Menganalisis Nilai-nilai Moral dari Karakter Desiree dalam Cerita Pendek (Désirée's Baby) oleh Kate Chopin - Intan Intan; Hening Putri Wayah Ratrie; Leni Dwi Astuti (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
Etymologically, the word moral comes from the Latin mos, which means the customs that a person has towards the people around him. Meanwhile, the general meaning is the norms of life that are carried out in order to maintain the level of social order in life. Moral values ​​in general are points related to good and bad behavior that guide a person's life. Therefore, this research was created to describe the moral values ​​of "Desiree" the main character in the short story "Désirée's Baby" in 1893. Analysis of this journal emphasizes the moral message that the author wants to convey to readers through analysis of the story's characters. In this story the main character Desiree presents a series of complex and deep moral values. The aim of this research is to find out and understand what moral values ​​are contained in the short story so that readers can emulate and learn from them for life.